Outcomes of 10 mg Rivaroxaban in Nonvalvular Atrial Fibrillation Patients With CrCl≥50 mL/min: A Retrospective Cohort Study - Qing Yan; Yide Yuan; Jiaqi Liang; Yuyang Zhao; Yuan Li; Jiali Fan; Jiahong Xue; Qiangsun Zheng (Cardiovascular Therapeutics, 2025)
Conclusion: For NVAF patients with CrCl≥50 mL/min in China, low-dose rivaroxaban (10 mg/day) is a viable alternative to standard doses in preventing IS/SE. In nonoverweight patients (BMI<24 kg/m2), it offers comparable efficacy with enhanced safety.